Determination of total phenolic content in dichloromethane extract of Phyuanthus acidus, Averrhoa bilimbi and Averrhoa carambola using folin ciocalteau method / Siti Wahila Abu Hassan - Abu Hassan, Siti Wahila (Faculty of Applied Sciences, 2009)
Three types of fruits which is Phyllathus acidus, Averrhoa bilimbi and Averrhoa carambola were studied by TPC method using Gallic Acid as a standard. The fresh Averrhoa carambola was purchased from Giant hypermarket, Shah Alam, while the other two fruits, Phyllanthus acidus and Averrhoa carambola were collected from Shah Alam and Kuala Selangor respectively. All of the fruits were performed in dry form by using oven dried method. From the data, it show that Averrhoa carambola has the highest TPC value which is 58.77 mg GAE/g dry sample compared to Averrhoa bilimbi with 32.74 mg GAE/g dry sample and the lowest TPC value among these fruits is Phyllanthus acidus with 10.56 mg GAE/g dry sample. Therefore, it shown that Averrhoa carambola was very effective in supplying natural antioxidant to protect against cellular damage.